Julian of Norwich: a very brief history - Ramirez, Janina (SPCK Publishing, 2016)
Part One: The History (What do we know?) This brief historical introduction to Julian of Norwich explores the social, political and religious factors that formed the original context of her life and writings, and considers how those factors affected the way she was initially received. What was her impact on the world at the time and what were the key ideas and values connected with her? Part Two: The Legacy (Why does it matter?) This second part explores the intellectual and cultural 'afterlife' of Julian of Norwich, and considers the ways in which her impact has lasted and been developed in different contexts by later generations. Why is she still considered important today? In what ways is her legacy contested or resisted? And what aspects of her legacy are likely to continue to influence the world in the future? The book has a brief chronology at the front plus a glossary of key terms and a list of further reading at the back